Technology choice and environmental regulation under asymmetric information - D'Amato, Alessio; Dijkstra, Bouwe (Elsevier, 2015)
We focus on the incentives of an industry with a continuum of small firms to invest in a cleaner technology under two environmental policy instruments: tradable emission permits and emission taxation. We assume asymmetric information, in that the firms' abatement costs with the new technology are either high or low. Environmental policy is set either before the firms invest (commitment) or after (time consistency). Under commitment, the welfare comparison follows a modified Weitzman rule, featuring reverse probability weighting for the slope of the marginal abatement cost curve. Both instruments can lead to under- or overinvestment ex post. Tradable permits lead to less than optimal expected new technology adoption. Under time consistency, the regulator infers the cost realization and implements the full-information social optimum.